Financial Cycles Around the World - Amat Adarov (The Vienna Institute for International Economic Studies (wiiw), 2018)
The study analyses financial cycles based on a global sample of 34 advanced and developing countries over the period 1960Q1 to 2015Q4. We use dynamic factor models and state-space techniques to estimate financial cycles in credit, housing, bond and equity markets, as well as aggregate financial cycles for each country in the sample using a large number of variables conveying price, quantity and risk characteristics of respective markets. The analysis reveals the highly persistent and recurring nature of financial cycles, which tend to fluctuate at frequencies much lower than business cycles, 9‑15 years on average, and are indicative of major financial distress episodes. Our results point to notable intra-regional synchronisation, as well as nontrivial co-movement tendencies between European, American and Asian financial cycles. We also extract global and regional financial cycles, the former closely associated with the dynamics of the US T-bill rate and the VIX index, confirming the existence of common supranational factors governing the boom-bust dynamics of financial market activity around the world.
Keywords: E44; E50; F37; G15; 330; financial cycles; global and regional financial cycles; asset bubbles; housing prices; equity; debt securities; credit; capital markets; Kalman filter; factor models